Developmental Dyslexia and Specific Language Impairment Same or Different. (Articles ). - Bishop, Dorothy V. M.
Developmental Dyslexia and specific language impairment (SLI) were for many years treated as distinct disorders but are now often regarded as different manifestation of the same underlying problem, differing only in severity or developmental stage. The merging of these categories has been motivated by the reconceptualization of dyslexia as a language disorder in which phenological pocessing is deficient. The authors argue that this focus underestimates the independent influence of semantic and syntactic deficits, which are widespread in SLI and which affect. reading comprehension and impair attainment of fluent reading in adolescence. The authors suggest that 2 dimensions of impairment are needed the relationship between these disorders and to capture phenotypic features that are important for identifying neurobiologically and etiologically coherent subgroups. --(from the author)